Evaluation of the Corrosion Behavior of Inconel 718 Alloy Processed by SLM Additive Manufacturing Method After 5000 h of Immersion in Natural Seawater - Elena Ionela Neacsu; Cristina Donath; Loredana Preda; Mihai Anastasescu; Alexandra Banu; Alexandru Paraschiv; Adrian Bibis; Maria Marcu (Metals, 2025)
The corrosion behavior of Inconel 718 alloy, developed through two different methods—forging (S1) and additive manufacturing (S2)—was evaluated in a seawater environment, and the results were compared with those of Inconel 825 alloy (S3). The corrosion performance of the alloys was examined according to ISO 8044/2024, using open circuit potential (OCP), potentiodynamic polarization (PP), and electrochemical impedance spectroscopy (EIS), in natural seawater at 25 °C over an extended immersion period. After 5000 h of immersion, the corrosion rate (Rcorr) estimated from anodic polarization tests was found to be lower for the wrought Inconel 718 alloy (1.21 µm y−1) compared to the wrought 825 alloy (4.1 µm y−1) and to the SLM Inconel 718 alloy (35.1 µm y−1), indicating high corrosion resistance for wrought Inconel 718. A morphological analysis of the alloy’s surface conducted using scanning electron microscopy (SEM) coupled with energy-dispersive X-ray spectroscopy (EDS) revealed a continuous, compact film with localized salt deposits on wrought Inconel 718 and Incoloy 825. In contrast, SLM Inconel 718 exhibited a porous, inhomogeneous film, leading to reduced protective capabilities and lower corrosion resistance. The results demonstrate that wrought Inconel 718 exhibits excellent corrosion resistance in seawater, making it a promising alloy for marine applications.